2017
DOI: 10.1186/s12959-017-0152-2
|View full text |Cite
|
Sign up to set email alerts
|

Video-assisted Thoracoscopic surgery (VATS) lobectomy for lung cancer does not induce a procoagulant state

Abstract: BackgroundChanges in the coagulation system in patients undergoing surgery for lung cancer have been sparsely investigated and the impact of the surgical trauma on the coagulation system is largely unknown in these patients. An increased knowledge could potentially improve the thromboprophylaxis regimes. The aim of this study was to assess the coagulation profile evoked in patients undergoing curative surgery by Video-Assisted Thoracoscopic Surgery (VATS) lobectomy for primary lung cancer.MethodsThirty-one pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…Interestingly, our study indicates that Video-Assisted Thoracoscopic Surgery (VATS) (compared to thoracotomy) can increase the risk of IDDVT [OR (95% CI) 8.41 (1.25-56.75)]. Several large studies that addressed incidences of VTE in patients following VATS, reported a relative decrease in risk for vein thrombosis associated with this method, as compared to thoracotomy (55,56). However, according to these studies, surgical approach cannot serve as an independent predictor of VTE (56).…”
Section: Discussionmentioning
confidence: 73%
“…Interestingly, our study indicates that Video-Assisted Thoracoscopic Surgery (VATS) (compared to thoracotomy) can increase the risk of IDDVT [OR (95% CI) 8.41 (1.25-56.75)]. Several large studies that addressed incidences of VTE in patients following VATS, reported a relative decrease in risk for vein thrombosis associated with this method, as compared to thoracotomy (55,56). However, according to these studies, surgical approach cannot serve as an independent predictor of VTE (56).…”
Section: Discussionmentioning
confidence: 73%
“…Inclusion of benign disease patients, protocol of LMWH administration and stage of tumor possibly resulted in the different conclusion. Besides, a study containing 31 patients without receiving thromboprophylaxis measured perioperative coagulation state by standard coagulation tests and rotational thromboelastometry and concluded VATS surgery for lung cancer showed little influence on coagulation profile while some coagulable variables were affected actually [25]. This conclusion was completely different from routine view of cancer surgery patients characterized with high VTE risk.…”
Section: Discussionmentioning
confidence: 94%
“…This conclusion was completely different from routine view of cancer surgery patients characterized with high VTE risk. The small study [25] was only extracted from another big trial which could bring in selection bias and there was lack of direct comparison of administration of LMWH. Moreover, the conclusions may be resulted from the extremely small sample in those studies.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, one case received secondary VATS to do hemostasis in PL group, she also recovered successfully after second surgery and discharged. Christensen et al found patients undergoing VATS lobectomy were normocoagulable preoperatively and VATS had no significant effect on the coagulation system (20). Attaran et al also reported not all lung cancer patients were in hypercoagulable state, meanwhile administration of LMWH once or twice one day even could not provide sufficient thromboprophylaxis for lung cancer patients who were indeed in hypercoagulable status, suggesting the critical need of careful screening of coagulation state of patients before administration of anticoagulation agents (19).…”
Section: Discussionmentioning
confidence: 99%